Perspectives of the institutionalization of homosexuality in Africa : Case of the Democratic Republic of Congo. - (:unkn) unknown (My University, 2018)
While legalized in other countries, homosexual marriage remains poorly perceived in Africa. With the exception of South Africa, which has made enormous progress on gay rights, other African states still oppose homosexual marriage and homosexuals are rejected and stigmatized. In this context, where homophobic sentiment is widespread and in the face of pressure from Western powers demanding that human rights, including those of homosexuals be respected, questions the perspectives of the institutionalization of homosexuality in Africa becomes interesting. Hence this article entitled « Perspectives of the institutionalization of homosexuality in Africa. Case of the Democratic Republic of Congo ». Following our participation-observation and analysis of the results of our research conducted in the city of Lubumbashi in the Democratic Republic of Congo, we noticed that homosexuality is still poorly perceived in the Democratic Republic of Congo and generally in Africa. Congolese are still trying for the moment to cling to their moral and cultural values that reject homosexuality. In these days, it would be wrong to initiate a law institutionalizing homosexual marriage. However, the Congolese and African political leaders would not try to take a law criminalizing homosexuals for fear of being accused by the Western powers of supporting human rights violations, which will lead to sanctions.
Keywords: African Research